Long-Term Risk of Infective Endocarditis After Transcatheter Aortic Valve Replacement - Butt, Jawad H; Ihlemann, Nikolaj; De Backer, Ole; Søndergaard, Lars; Havers-Borgersen, Eva; Gislason, Gunnar H; Torp-Pedersen, Christian; Køber, Lars; Fosbøl, Emil L (Journal of the American College of Cardiology, 2019)
Patients undergoing surgical aortic valve replacement (SAVR) are considered at high risk of infective endocarditis (IE). However, data on the risk of IE following transcatheter aortic valve replacement (TAVR) are sparse and limited by the lack of long-term follow-up as well as a direct comparison with patients undergoing SAVR. This study sought to investigate the long-term incidence of IE in patients undergoing TAVR and to compare the long-term risk of IE with patients undergoing isolated SAVR. In this nationwide observational cohort study, all patients undergoing TAVR and isolated SAVR from January 1, 2008, to December 31, 2016, with no history of IE and alive at discharge were identified using data from Danish nationwide registries. A total of 2,632 patients undergoing TAVR and 3,777 patients undergoing isolated SAVR were identified. During a mean follow-up of 3.6 years, 115 patients (4.4%) with TAVR and 186 patients (4.9%) with SAVR were admitted with IE. The median time from procedure to IE hospitalization was 352 days (25th to 75th percentile: 133 to 778 days) in the TAVR group and 625 days (25th to 75th percentile: 209 to 1,385 days) in the SAVR group. The crude incidence rates of IE were 1.6 (95% confidence interval [CI]: 1.4 to 1.9) and 1.2 (95% CI: 1.0 to 1.4) events per 100 person-years in TAVR and SAVR patients, respectively. The cumulative 1-year risk of IE was 2.3% (95% CI: 1.8% to 2.9%) and 1.8% (95% CI: 1.4% to 2.3%) in TAVR and SAVR patients, respectively. Correspondingly, the cumulative 5-year risk of IE was 5.8% (95% CI: 4.7% to 7.0%) and 5.1% (95% CI: 4.4% to 6.0%), respectively. In multivariable Cox proportional hazard analysis, TAVR was not associated with a statistically significant different risk of IE compared with SAVR (hazard ratio: 1.12; 95% CI: 0.84 to 1.49). The 5-year incidence of IE following TAVR was 5.8% and not significantly different than the incidence following SAVR.